Hydrolysis of cellulose derived from steam exploded bagasse by penicillium cellulases: comparison with commercial cellulase - Singh, Rajkumar; Varma, Anjanikumar; Laxman, Ryali Seeta; Rao, Mala (Bioresource Technology, 2009)
A complete cellulase from Penicillium pinophilum was evaluated for the hydrolysis of a-cellulose derived from steam exploded sugarcane bagasse and other cellulosic substrates. alpha-Cellulose at 1% substrate concentration was completely hydrolyzed by Penicillium cellulase within 3 h wherein at 10% the hydrolysis was 100% within 24 h with an enzyme loading of 10 FPU/g. The hydrolysate yielded glucose as major end product as analyzed by HPLC. Under similar conditions, hydrolysis of Sigmacell (microcrystalline cellulose), CP-123 (pulverized cellulose powder) and ball milled Solka Floc were 42%, 56% and 52%, respectively. Further the hydrolysis performance of Penicillium sp. cellulase is compared with Trichoderma reesei cellulase (Accellerase (TM) 1000) from Genencore. The kinetics of hydrolysis with respect to enzyme and substrate concentration will be presented. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Accellerase (TM) 1000; Enzymatic hydrolysis; High beta-glucosidase; Penicillium cellulase; Sugarcane bagasse